Tadalafil: 15 years' journey in male erectile dysfunction and beyond. Issue 6 (13th December 2018) - Ahmed, Nermin S.
Abstract: Tadalafil, Cialis, Eli Lilly & Co./ICOS, (6 R, 12a R )‐6‐(1, 3‐benzodioxol‐5‐yl)‐2‐methyl‐2, 3, 6, 7, 12, 12a‐hexahydropyrazino[1′, 2′:1, 6] pyrido[3, 4‐ b ]indole‐1, 4‐dione, was first discovered in 2003. It was reported to have high diastereospecificity for phosphodiesterase 5 (PDE5) inhibitions. The cis‐ (6 R, 12a R ) enantiomer is the most active enantiomer. Tadalafil showed PDE5 inhibition with IC50 = 5 nM. It possesses high selectivity for PDE5 versus PDE1‐4 and PDE6. Tadalafil is more selective to PDE5 against PDE6 whereas sildenafil, another commercially available PDE5 inhibitor shows similar potencies to inhibit PDE5 and PDE6. Tadalafil is used for the treatment of male erectile dysfunction (MED), prostatic benign hyperplasia (PBH) signs and symptoms, and pulmonary arterial hypertension (PAH). Adcirca, another name for tadalafil, is used to treat PAH and improve exercise capacity. Recent clinical studies suggest the use of tadalafil for nonurological applications, including circulatory disorders (ischemia injury, myocardial infarction, cardiac hypertrophy, cardiomyopathy, heart failure, and stroke), neurodegenerative disorders, and cognitive impairment conditions. This review discusses tadalafil and its analogues reported in the past 15 years. It discusses synthetic pathways, structural activity relationships, existing and future pharmacological indications of tadalafil and its analogues. This work can help medicinal chemists developing novel PDE5 inhibitors with wider therapeutic indications.